PROCEDURAL POSITION OF A DOCTOR DURING EXAMINATION OF A CORPSE - ZASHLYAPIN LEONID (Legal Bulletin)
The article is devoted to the analysis of the procedural position of a doctor during the examination of a corpse in modern criminal proceedings. Its relevance is due to the normative and doctrinal uncertainty of the status of this participant in criminal proceedings, associated with the absence of special rules that would establish his rights, duties and responsibilities.